Heterogeneity versus Homogeneity in Schools: A Study of the Educational Value of Classroom Interaction - Daniel Gabaldón-Estevan (MDPI AG, 2020)
The degree of homogeneity and heterogeneity among schools affects the comprehensiveness and inclusiveness of the school system and the type and scope of classroom interaction. Since the beginning of the 1980s, interest has gradually increased in the effects of homogeneity and heterogeneity of schools on classroom interactions; this research involves various disciplines and has different goals. The present paper contributes to academic debate on the often ignored consequences of socialisation of pupils with diversity. In particular, we revise the evidence on the effect of socialisation (or lack of it) with diversity resulting from the degree of homogeneity or heterogeneity to which school children are exposed through their interactions in the classroom. We aim, in particular, to shed light on what the assumed value of classroom interactions as an argument in favour or either heterogeneous or homogeneous groups. We review work analysing school homogeneity in relation to age, gender, ethnicity and disability and the effect on classroom interactions. Most studies concur with current achievement motivation theories, which highlight the important role of context and agents of socialisation, such as classroom peers, in the development of pupils' beliefs and behaviours. Studies that find support for classroom homogeneity tend to focus narrowly on academic performance, whereas findings that support classroom heterogeneity tend to analyse higher order values such as equity and inclusiveness. The findings in the literature suggest, furthermore, that children's experiences of exclusion and diversity influence their friendship decision-making, suggesting that heterogeneous schools promote a more inclusive society.